SINERGITAS HUKUM ISLAM DAN HUKUM ADAT: ANALISIS TERHADAP TRADISI KEPENG PELENGKAK DALAM PERNIKAHAN MASYARAKAT DI DESA MONGGAS - Lalu Yoga Vandita; Lalu Yogi Mandala Putra (BEGIBUNG: Jurnal Penelitian Multidisiplin, 2026)
Islamic law and custom are interconnected legal aspects in the formation of a law, one of which is found in marriage law. Islamic law and custom have their respective involvement in the process of making a law. In practice, there is an interaction between customary law and Islamic law, which often results in adaptation or acculturation in the implementation of marriage, for example. In various regions, marriage has different traditions and its own uniqueness. One of the marriage phenomena that occurs in Sasak customs is stepping over older siblings, one of the issues often encountered in Sasak society, especially in Monggas village which still upholds traditional values. To facilitate research, researchers used a qualitative approach in this study aimed to understand in depth the social phenomenon in the form of the implementation of customs and regulations in the implementation of marriage in Monggas Village. Islamic law and Custom go hand in hand, customs resolve social affairs, Islam legitimizes Sharia matters. Kepeng pelengkak aims to honor siblings and maintain islaturahmi, such things are highly recommended in Islam.